2021
DOI: 10.3390/sym13060921
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Data Hiding in Encrypted Images Using Median Edge Detector and Two’s Complement

Abstract: With the rapid development of cloud storage, an increasing number of users store their images in the cloud. These images contain many business secrets or personal information, such as engineering design drawings and commercial contracts. Thus, users encrypt images before they are uploaded. However, cloud servers have to hide secret data in encrypted images to enable the retrieval and verification of massive encrypted images. To ensure that both the secret data and the original images can be extracted and recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…RDH schemes are also explored for use with different image datasets, such as natural images [42], medical images [43], etc. Though many RDH schemes have been described in the literature [44,45], RDH techniques which operate in an encrypted medium [16,46] have become widely accepted due to their wide range of practical applications pertaining to the security of the cover medium.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…RDH schemes are also explored for use with different image datasets, such as natural images [42], medical images [43], etc. Though many RDH schemes have been described in the literature [44,45], RDH techniques which operate in an encrypted medium [16,46] have become widely accepted due to their wide range of practical applications pertaining to the security of the cover medium.…”
Section: Related Workmentioning
confidence: 99%
“…RDH can be implemented on a natural image [12][13][14][15] or over an encrypted image [16][17][18]. Drawbacks of using natural images as the cover image include:…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al [26] used the AMBTC technique for data embedding, although not in the RDHEI domain. Further, it has been observed that the AMBTC technique is a popular lossy compression technique which has been widely used in data hiding [14,[36][37][38]. As far as working method of [33] is concerned, Su et al's technique first scrambles and then compresses the host image into triplets in a block-wise manner, where each triplet includes two quantization level (high & low) and a bitmap.…”
Section: Related Workmentioning
confidence: 99%
“…The multimedia type includes video files of any format, audio files of any format, and image files. [1][2][3][4][5][6] The objective of this steganography technique is to share the information in a secret way that ensures privacy over the internet. This can also lead to a few advantages, including copyright preservation, detection of tampering image authentication and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Steganography is a method of hiding information into any digital media files, or in simple terms, it is known as multimedia. The multimedia type includes video files of any format, audio files of any format, and image files 1‐6 . The objective of this steganography technique is to share the information in a secret way that ensures privacy over the internet.…”
Section: Introductionmentioning
confidence: 99%